Ophthalmic Complications of Bariatric Surgery - Azevedo Guerreiro, R (2014)
Obesity is increasing vastly in the world, and the number of bariatric surgeries being performed is also increasing. Patients being submitted to bariatric surgeries, especially malabsorptive procedures, have an increased risk of developing nutrient deficiencies, which can culminate in symptomatic hypovitaminosis, if supplementation is not done correctly. The eye and the optic system need an adequate level of several vitamins and minerals to perform properly, especially vitamin A, and this article wants to cover the main nutrients involved, the possible ophthalmic complications that can arise by their deficiency, and the management of those complications.